La trajectoire professionnelle des personnes de type artistique - Riverin, Danielle; Brassard, Sylvie; Simard, Yanik; Michaud, Clémence (Canadian Journal of Counselling and Psychotherapy, 2007)
The uniqueness that artists tend to demonstrate throughout their working lives has always fascinated specialists in career counselling. Above and beyond this uniqueness can we identify some meeting points? This present article aims precisely identifying common elements of the vocational trajectory of about a hundred artistic types at different moments in their career. The elements should permit every counsellor, working with artists, to better understand particular traits of their vocational development and to elaborate more adapted help programs.